Bank Lending Rate Determinants: Evidence from Nepalese Commercial Banks - Acharya, Tej Prasad (Damak Campus Journal, 2025)
This empirical study investigates the determinants of lending interest rates in Nepalese commercial banks, utilizing panel data spanning fiscal years 2073/74 to 2080/81. Employing multiple linear regression and correlation analyses, the research examines the influence of key financial variables—namely, interest rate on deposits, impairment charge rate, operating expenses, and non-operating expenses—alongside macroeconomic indicators such as inflation and economic growth. The findings reveal that the interest rate on deposits exerts a statistically significant positive effect on lending rates, indicating its central role in banks’ pricing strategies. Inflation also demonstrates an important moderating influence, suggesting that lending rates are responsive to macroeconomic price dynamics. Conversely, impairment charges, operating and non-operating expenses, and economic growth did not exhibit significant linear associations. The financial model accounted for 92.6% of the variance in lending rates, reflecting high explanatory power. These results offer valuable insights into the cost-driven nature of interest rate formation and the sensitivity of lending behavior to inflation, with implications for monetary policy and financial regulation in emerging economies.